The ecology of browsing and grazing - Prins, H. H. T. (Springer, 2017)
Grazers and Browsers in a Changing World -- An Evolutionary History of Browsing and Grazing Ungulates Christine Janis -- The Morphophysiological Adaptations of Browsing and Grazing Mammals Marcus Clauss, Thomas Kaiser, and Jürgen Hummel...